Aligned deposition and electrical measurements on single DNA molecules. (5th November 2015) - Eidelshtein, Gennady; Kotlyar, Alexander; Hashemi, Mohtadin; Gurevich, Leonid
Abstract: A reliable method of deposition of aligned individual dsDNA molecules on mica, silicon, and micro/nanofabricated circuits is presented. Complexes of biotinylated double stranded poly(dG)–poly(dC) DNA with avidin were prepared and deposited on mica and silicon surfaces in the absence of Mg 2+ ions. Due to its positive charge, the avidin attached to one end of the DNA anchors the complex to negatively charged substrates. Subsequent drying with a directional gas flow yields DNA molecules perfectly aligned on the surface. In the avidin–DNA complex only the avidin moiety is strongly and irreversibly bound to the surface, while the DNA counterpart interacts with the substrates much more weakly and can be lifted from the surface and realigned in any direction. Using this technique, avidin–DNA complexes were deposited across platinum electrodes on a silicon substrate. Electrical measurements on the deposited DNA molecules revealed linear IV -characteristics and exponential dependence on relative humidity.